A contentious intervention to support the medical workforce: a case study of the policy of introducing physician associates in the United Kingdom - Martin McKee; Louella K. Vaughan; Giuliano Russo (Human Resources for Health)
Abstract Background Health systems across Europe are facing a workforce crisis, with some experiencing severe shortages of doctors. In response, many are exploring greater task-sharing, across established professions, such as doctors, nurses, and pharmacists, with patients and carers, and with new occupational groups, in particular ones that can assist doctors and relieve their workload. Case presentation In the early 2000s the United Kingdom created a new occupational role, that of physician assistant. They had a science degree and then underwent a 2-year postgraduate training course. The name soon changed, to physician associate, and the range of roles and responsibilities expanded greatly, although in a largely unregulated manner; by 2024, some were undertaking complex procedures or managing undifferentiated patients in primary care. Catalysed by some high-profile failings, this expansion has generated major concerns, over patient safety and consent, the scope of practice and preferential employment conditions of this group, the adverse consequences for medical training, and the additional medical workload involved in supervision. This has led to a widespread grassroots backlash by the medical profession, often challenging their leaders who had supported this idea. As a consequence, professional bodies that were initially in favour are now expressing serious concerns and it seems likely that the roles and responsibilities of physician associates (and related occupations) will be curtailed. We review published literature and official documentation about this policy to understand the drivers of its development, its benefits, and risks. Conclusions The experience in the UK offers cautionary lessons for other European countries contemplating similar ideas. It underscores the importance of maintaining trust with those affected by change, undertaking a detailed systems analysis with attention to risks of unintended consequences, agreeing clear role definitions, providing adequate regulatory oversight, and the need to avoid damaging training of future doctors. This case study highlights the need for a carefully thought-out approach that considers both the potential benefits and pitfalls of integrating new roles like physician associates into a healthcare system. The failure to do so has created a new occupational group with unrealistic expectations and has further demoralised an already unhappy medical profession.